Estudo da variável (nj) em paroxítonas terminadas em “nia” e “nio” em Manaus: descrição da tese - Belmonte dos Santos Rodrigues, Tatiana (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The study of the variable (nj) in paroxitones terminated in "nia" and "nio" inManaus is the subject of the thesis that is running in the Graduate Program in Linguistics at the Federal University of Minas Gerais, concentrated in the area of Theoretical and Descriptive Linguistics. This study aims to verify evidence of the palatalization process as occurred in the transition from Latin to Portuguese, through the achievements of variants that characterize this process. The purpose of this article is to describe the research developed in the thesis, pointing its general aspects, such as justification, assumptions, goals and theoretical and methodological framework.
Keywords: Variable (nj).; Palatalization; Linguistics